Prevalence and potentially prognostic value of C‐circles associated with alternative lengthening of telomeres in canine appendicular osteosarcoma. (8th December 2020) - Bicanova, Ludmila; Kreilmeier‐Berger, Theresa; Reifinger, Martin; Holzmann, Klaus; Kleiter, Miriam
Abstract: Alternative lengthening of telomeres (ALT) is a telomerase‐independent telomere maintenance mechanism (TMM) with high prevalence in human osteosarcomas but remains unknown in canine osteosarcomas. The aim of this study was to evaluate the prevalence of ALT by detection of extra‐chromosomal circles of telomeric DNA and to assess clinical outcome in canine patients with spontaneous occurring appendicular osteosarcoma. Fifty dogs with histopathological confirmed osteosarcomas were included into this study. Medical records were retrospectively analysed for patient characteristics, oncologic therapy and survival. DNA was isolated from archived FFPE tumour tissue specimens and applied for C‐ and G‐circle assay (CCA and GCA) and for telomeric content (TC) measurement with radiolabeled probes. ALT activity was detected for 10 of 50 (20%) cases by CCA. Four CCA positive cases were detected even with input DNA below 1 ng and demonstrated the high sensitivity of CCA for canine tumours. G‐circles and TC were not suitable to distinguish CCA positive and negative cases. CCA‐status showed an association with male gender and Rottweiler breed. Dogs with CCA positive osteosarcomas had shorter overall survival times than patients with CCA‐tumours and CCA‐status was a significant prognostic factor besides treatment in the Cox proportional hazard model. These findings make canine osteosarcomas an interesting model for comparative TMM research, but future studies are warranted to investigate if CCA‐status can serve as novel prognostic marker.